Once upon a broken heart ebook - Garber, Stephanie (Once Upon a Broken Heart, 2021)
#1 NEW YORK TIMES BESTSELLER! ONCE UPON A BROKEN HEART marks the launch of a new series from Stephanie Garber about love, curses, and the lengths that people will go to for happily ever after For as long as she can remember, Evangeline Fox has believed in true love and happy endings . . . until she learns that the love of her life will marry another. Desperate to stop the wedding and to heal her wounded heart, Evangeline strikes a deal with the charismatic, but wicked, Prince of Hearts. In exchange for his help, he asks for three kisses, to be given at the time and place of his choosing. But after Evangeline's first promised kiss, she learns that bargaining with an immortal is a dangerous game — and that the Prince of Hearts wants far more from her than she'd pledged. He has plans for Evangeline, plans that will either end in the greatest happily ever after, or the most exquisite tragedy. Also by Stephanie Garber: The Caraval Series - Caraval - Legendary - Finale